2014
DOI: 10.1111/1750-3841.12416
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Activities in Extracts of Fully Grown Cladodes of 8 Cultivars of Cactus Pear

Abstract: The antimicrobial and antioxidant activities of some cultivars of the nopal cactus have not been determined. In this study, 8 cultivars of nopal cacti from Mexico were assayed for phenolic content, antioxidant activities, and antimicrobial activities against Campylobacter Jejuni, Vibrio cholera, and Clostridium Perfringens. Plant material was washed, dried, and macerated in methanol. Minimum bactericidal concentrations (MBCs) were determined using the broth microdilution method. Antioxidant activities were qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
1
23
1
2
Order By: Relevance
“…Several studies have been carried out with cactus stems which quantify their antioxidant capacity using DPPH • , ABTS •+ or as total phenol content. Sanchez et al . found that cladodes showed a low ability to catch the DPPH • radical in a range of 19–40%; this response can be explained by the widespread presence of monohydroxylated phenolic compounds according to Gallegos et al .…”
Section: Chemical Composition Changes Of Cactus Stemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been carried out with cactus stems which quantify their antioxidant capacity using DPPH • , ABTS •+ or as total phenol content. Sanchez et al . found that cladodes showed a low ability to catch the DPPH • radical in a range of 19–40%; this response can be explained by the widespread presence of monohydroxylated phenolic compounds according to Gallegos et al .…”
Section: Chemical Composition Changes Of Cactus Stemsmentioning
confidence: 99%
“…Among the biofunctional compounds reported, the presence of fiber, hydrocolloids, phenolics, chlorophyll, carotenoids, calcium and vitamin C stand out . Some of these compounds enable cladodes to inhibit reactive oxygen species (ROS) by up to 40% . Therefore, these biologically active components provide health benefits and reduce the risk of chronic degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Nunes et al, 2014) y en cladodios del género Opuntia (Ginestra et al, 2009;Sánchez et al, 2014), especie que las personas tienen el costumbre de comer el cladodio. Esta falta de interés económico en especies del género Melocactus, pueden cambiar con el desarrollo de los estudios etnobotánicos, reportando los más diversos usos en la medicina de los pueblos tradicionales (Alves & Nascimento, 2010;Lucena et al, 2013;Lucena et al, 2014) en colaboración con los estudios farmacológicos y la estandarización de las técnicas y metodologías utilizadas en estos análisis.…”
Section: Resultados Y Discusiónunclassified
“…Estudios sobre los compuestos bioactivos en varios vehículos (Corral-Aguayo et al, 2008), se están realizando, sobre todo en especies pertenecientes a las regiones áridas, la lucha diaria contra las condiciones más adversas, tales como la falta de agua, la luz del sol excesiva, ataques de plagas y enfermedades (Cuchillo et al, 2013), tratando de encontrar elementos que naturalmente están presentes y pueden actuar directamente en los alimentos, que manifiesten las propiedades medicinales y dietéticas (Ginestra et al, 2009;Dehbi et al, 2013;Sánchez et al, 2014).…”
Section: Resultados Y Discusiónunclassified